2022
DOI: 10.1021/acscatal.2c04668
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)–Thiazol-2-ylidenes: Highly Reactive N-Heterocyclic Carbenes for the Hydroboration of Terminal and Internal Alkynes. Ligand Development, Synthetic Utility, and Mechanistic Studies

Abstract: In the last 15 years, copper-catalyzed borylative transformations utilizing boryl–copper have been established as a powerful activation mode in organic synthesis and catalysis, enabling direct transformations of various π-systems. Although many of these transformations use NHC (N-heterocyclic carbene) ligands, these studies have been almost exclusively limited to the derivatives of imidazol-2-ylidenes. However, the molecular properties of N-aryl-imidazol-2-ylidenes, such as IPr (IPr = 1,3-bis(2,6-diisopropylph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…30−33 To date, the reported homogeneous Cu systems not only require ligands and bases but also bear high waste because of difficult recycling (Figure S30). 30,31,34,35 Despite several heterogeneous Cu catalysts such as Cu-MOFs, 36−38 Cu (oxides), 39−42 or Cu single atoms 43 have been utilized, the base or high reaction temperature is still necessary (Figure S30). Consequently, the design and synthesis of heterogeneous Cu-based catalysts for effective hydroboration of alkynes under mild and additive-free conditions are in great demand (Figure S30).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30−33 To date, the reported homogeneous Cu systems not only require ligands and bases but also bear high waste because of difficult recycling (Figure S30). 30,31,34,35 Despite several heterogeneous Cu catalysts such as Cu-MOFs, 36−38 Cu (oxides), 39−42 or Cu single atoms 43 have been utilized, the base or high reaction temperature is still necessary (Figure S30). Consequently, the design and synthesis of heterogeneous Cu-based catalysts for effective hydroboration of alkynes under mild and additive-free conditions are in great demand (Figure S30).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[34][35][36]39,44,45 And thus the activation of alkyne bonds on Cu sites will contribute to increasing the reaction activity. 35,46,47 However, in the absence of additives, the activation of B 2 Pin 2 to nucleophilic copper-boryl species is driven by the copper ethoxide (Cu-OEt) species generated from the dissociation of EtOH molecules on Cu coordination bonds, 43,48 with the result that the efficient ethanol dissociation proves to be another dominating step for lowering the reaction energy barrier. Therefore, if ethanol dissociation and alkyne activation are conducted in parallel within an ideal distance, the hydroboration reaction will be definitely promoted.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, we reported Ag(I)–thiazol-2-ylidene complexes and their application in the intramolecular cyclization to yield oxazolidines ( Scheme 5 ) [ 64 ]. The non-classical framework of thiazol-2-ylidene offers new opportunities in catalysis due to its differentiated half-umbrella-shaped ligand structure and enhanced p-electrophilicity [ 69 ]. We found that these Ag(I)–thiazol-2-ylidene complexes are highly active in the electrophilic cyclization of propargylic amides.…”
Section: Intramolecular Cyclizationsmentioning
confidence: 99%
“…[10,11] (3) The synthetic utility is further demonstrated in the late‐stage hydroboration of complex pharmaceuticals, enabling to introduce boron to drug molecules with excellent functional group tolerance [12] . (4) The most reactive Cu(I)‐NHC complex [9d,13] in this class has been commercialized in collaboration with MilliporeSigma to enable broad access of the synthetic chemistry community (no. 930873, NHC⋅HCl salts: no.…”
Section: Introductionmentioning
confidence: 99%